(untitled) (Academicia Globe: Inderscience Research, 2022)
The article investigates the process of interaction of orthosilicic acid obtained from quartz sand with isoamyl alcohol. Optimal synthesis conditions were found. The resulting products were identified by IR spectroscopy. The solubility of the obtained products in different solvents at room temperature was studied. The best molar ratio of silicic acid to alcohol and the best reaction time were found.